2016
DOI: 10.1080/10934529.2015.1128719
|View full text |Cite
|
Sign up to set email alerts
|

Environmental analysis of the life cycle emissions of 2-methyl tetrahydrofuran solvent manufactured from renewable resources

Abstract: An environmental analysis has been conducted to determine the cradle to gate life cycle emissions to manufacture the green solvent, 2-methyl tetrahydrofuran. The solvent is considered a greener chemical since it can be manufactured from renewable resources with a lower life cycle footprint. Analyses have been performed using different methods to show greenness in both its production and industrial use. This solvent can potentially be substituted for other ether and chlorinated solvents commonly used in organom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…In fact, MTHF has many benefits to THF as a solvent including immiscibility with water, lower volatile organic compound (VOC) emissions, and improved results in a variety of applications, particularly in the pharmaceutical industry . Furthermore, a life cycle analysis of the production of MTHF from furfural showed a 97% reduction in emissions compared to the current industrial route to make THF . THP also shows potential as a green alternative to THF or 1,4‐dioxane, having similar properties with the exception of its limited solubility in water, which could be advantageous in liquid‐liquid separation processes…”
Section: Products From C5 (Furfural)mentioning
confidence: 99%
“…In fact, MTHF has many benefits to THF as a solvent including immiscibility with water, lower volatile organic compound (VOC) emissions, and improved results in a variety of applications, particularly in the pharmaceutical industry . Furthermore, a life cycle analysis of the production of MTHF from furfural showed a 97% reduction in emissions compared to the current industrial route to make THF . THP also shows potential as a green alternative to THF or 1,4‐dioxane, having similar properties with the exception of its limited solubility in water, which could be advantageous in liquid‐liquid separation processes…”
Section: Products From C5 (Furfural)mentioning
confidence: 99%
“…The solvent selected, 2-methyltetrahydrofuran, although still lacking classification by pharmaceutical regulatory boards such as the FDA, is a significantly greener option. 61 In this regard, the process reported here relies entirely on class 3 FDA solvents, i.e., solvents recognized for the low toxic potential thus facilitating the straightforward application of our work to the industrial setting. 52 Another important consideration to determine the practicality of a synthesis is cost.…”
Section: Discussion Based On Sustainability Metricsmentioning
confidence: 99%
“…2-Methyltetrahydrofuran, see Figure 11 , is an ethereal solvent that can be derived from renewable resources such as levulinic acid or furfural, 153 which can themselves be derived from agricultural waste such as corn stover, sugar cane bagasse, and rice straw. 154 Life cycle assessment conducted on 2-MeTHF has shown that production of the solvent from furfural derived from corn-cob waste can reduce emissions by up to 97% when compared to a traditional chemical synthesis of THF, 155 though it is not always clear how individual supplies of 2-MeTHF are currently made. Structurally, 2-MeTHF differs from THF by the addition of one single methyl group, yet this addition is responsible for several significantly different physiochemical properties.…”
Section: Selection Of Alternative Solventsmentioning
confidence: 99%